Perlindungan Konsumen Dari Aspek Hukum Pidana Terhadap Peredaran Kosmetik Ilegal: Studi Putusan Nomor 572/PID.SUS/2022/PN SMR - Deski Bertolens Tungga; Thelma S.M Kadja; Heryanto Amalo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
According to data obtained from the Food and Drug Supervisory Agency (BPOM), the total number of illegal cosmetics and/or containing prohibited/dangerous ingredients during the period from October 2021 to August 2022 was more than 1 million pieces with an economic value of IDR 34.4 billion. BPOM also followed up on findings based on reports from several drug and food supervisory authorities in other countries. Based on the report, as many as 46 (forty-six) cosmetics were withdrawn from circulation because they contained prohibited ingredients, microbial contamination, or were counterfeit cosmetics. During the same period, BPOM also carried out cyber patrols. This cyber patrol was carried out on website, social media, and e-commerce platforms to trace and prevent the circulation of illegal cosmetics and BPOM found and blocked (takedown) 83,700 links to the sale of illegal cosmetic products and containing prohibited/dangerous ingredients with a total product amount of 6.5 million pieces and an economic value of Rp 296.9 billion. This proves that there are still many illegal cosmetic products that contain harmful ingredients and do not have a distribution permit. This research is a normative legal research supported by a statutory approach (statute approcach) which uses secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials that collect laws and regulations related to the legal issues at hand, case studies, collecting books, journals, dictionaries and other related literature. The legal materials that have been successfully collected are analyzed, namely description, interpretation, evaluation and systematic. The results of this study show that (1) Based on the form of consumer protection from the criminal aspect, there are five forms of consumer protection, namely: Protection against Unsafe Products; Fraud and Fraud Violation of Clear and Correct Information; Violations of Consumer Rights; Abuse of Power or Dominant Position, as well as unfair business practices. Criminal sanctions aim to provide a deterrent effect to business actors who harm consumers. (2) Based on the perspective of criminal law, the actions of DM business actors who have circulated illegal cosmetics without a distribution permit in decision number 572/Pid.Sus/2022/PN Smr, violate the provisions of Article 197 of Law Number 36 of 2009 concerning Health, which has affirmed that every person who deliberately produces and/or distributes pharmaceutical preparations and/or medical devices without having a distribution permit as mentioned in Article 106 paragraph (1) is criminally punished imprisonment for a maximum of (fifteen) years and a maximum fine of Rp.1,500,000,000,- (one billion five hundred million rupiah).